Feasibility study of endoscopic biliary drainage under direct peroral cholangioscopy by using an ultra-slim upper endoscope (with videos) - Park, Jae Keun; Moon, Jong Ho; Lee, Yun Nah; Jo, Seok jung; Choi, Moon Han; Lee, Tae Hoon; Cha, Sang-Woo; Cho, Young Deok; Park, Sang-Heum (Endoscopy International Open, 2021)
The therapeutic utility of peroral cholangioscopy (POC) is limited. Direct POC using an ultra‑slim upper endoscope expands the therapeutic indications because of its larger working channel, of up to 2.2 mm. We evaluated the feasibility of selective biliary drainage using a plastic stent under direct POC. From April 2015 to March 2019, biliary drainage under endoscopic visualization was performed in the same endoscopic session as direct POC without exchanging the duodenoscope. After guidewire insertion through the stricture or stone, a 5 Fr plastic stent and/or nasobiliary drainage catheter was used for biliary drainage. Selective biliary drainage under direct POC was performed in 32 patients, including 17 with difficult bile duct stones. Biliary drainage was performed with a plastic stent in 29 patients, nasobiliary drainage in one, and combined drainage in two patients. The technical success rate for biliary drainage placement under direct POC was 100 % (32/32). No significant procedure-related complications occurred. In conclusion, biliary drainage with a plastic stent or catheter under direct POC using an ultra-slim upper endoscope is feasible and may be useful for lesions obstructing the bile duct.